Large-scale monitoring of Indo-Pacific finless porpoises (Neophocaena phocaenoides) using multiple static acoustic sensors - Caruso, Francesco; Giorli, Giacomo; Dong, Lijun; Zhao, Likun; Liu, Mingming; Lin, Mingli; Li, Songhai (Frontiers in Remote Sensing, 2022)
The distribution of Indo-Pacific finless porpoise (IPFP, Neophocaena phocaenoides) around the Hainan Island (China) is unknown, but evidences for a resident population have recently emerged. Passive acoustic data were collected from 10 locations along the south-west area of the island using static sensors (about 200 km of coastline), over a total period of 476 days from 25th February 2018 to 16th June 2019 (154,884 five-minute recordings). A supervised machine learning technique was used to classify IPFP clicks and acoustic features were measured for 2,654 short-narrowband pulses detected within 47 days across the 10 sites. Detections were verified by a trained operator using spectrogram analysis and the detection range of the clicks was estimated using a Transmission Loss (TL) model. The animals were not detected at all locations and the site with the highest number of detections was characterized by low levels of ambient noise, abundance of soniferous fishes and the presence of another marine mammal species, the Indo-Pacific humpback dolphin (Sousa chinensis). The northernmost region had no detections and only two recorded files containing IPFP clicks were found at the two nearby locations (one file each). In general, the low number of detections in the study area are most likely a result of the limited detection range (about 200 m) of IPFP echolocation signals. This is a nationally protected species and the Hainan population is increasingly subject to many threats. The large-scale and long-term monitoring approach provides information regarding the spatial acoustic occurrence of this vulnerable, nearshore and small-size cetacean.